Exploring The Relationship Between Private Tutoring And Mathematics Achievement Among Qatari Primary School Students - Hentati, Imen (Technium Social Sciences Journal, 2024)
This study aims to shed light on the association between private tutoring and academic achievement in mathematics among primary school students in Qatar. Utilizing data from the Trends in International Mathematics and Science Study (TIMSS) 2019, we employ a propensity score technique to elucidate the disparities in mathematics achievement levels between two distinct groups: students who receive private tutoring and those who do not. Our findings indicate that students who engage in private tutoring have lower odds of attaining higher achievement scores in mathematics. .